2019
DOI: 10.3389/fmicb.2019.01760
|View full text |Cite
|
Sign up to set email alerts
|

Quality Maintenance of Beef Burger Patties by Direct Addiction or Encapsulation of a Prickly Pear Fruit Extract

Abstract: Beef burger patties are a very perishable food product with a maximum shelf life of 3 days at 4°C, due to a fast decrease of quality parameters and microbial growth. Although some additives listed in the Regulation EU 601 (2014) are allowed in fresh minced beef and meat preparations with antioxidant functionality, no additive with antimicrobial activity is permitted. In this study, a prickly pear extract (PPE) was added to beef burger patty formulations both by direct application and encapsulation in alginate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…fluorescens has been exerted by almost all the PPJ samples, including those deriving from the white cultivar, suggesting that the antibacterial activity against these species is probably mainly due to the high presence of polyphenols. Such efficacy against Gram-negative bacterial species is of particular interest since most of the research studies have shown that Gram-positive bacteria are more susceptible towards plant extracts as compared to Gram negative ones [44][45][46][47]. The sensitivity to PPJ samples of targeted bacteria evinced in this study broadened the range of natural compounds able to act as food preservatives in replacement of the chemical ones.…”
Section: Antimicrobial Activity Of Ppjs Against Target Bacteriamentioning
confidence: 89%
“…fluorescens has been exerted by almost all the PPJ samples, including those deriving from the white cultivar, suggesting that the antibacterial activity against these species is probably mainly due to the high presence of polyphenols. Such efficacy against Gram-negative bacterial species is of particular interest since most of the research studies have shown that Gram-positive bacteria are more susceptible towards plant extracts as compared to Gram negative ones [44][45][46][47]. The sensitivity to PPJ samples of targeted bacteria evinced in this study broadened the range of natural compounds able to act as food preservatives in replacement of the chemical ones.…”
Section: Antimicrobial Activity Of Ppjs Against Target Bacteriamentioning
confidence: 89%
“…However, by-products obtained by fruits and vegetables possess antimicrobial properties due to their antioxidant activity and to the high content of total polyphenols and betalains [15][16][17], therefore, the addition of such ingredients in leavened bakery products, such as bread, could negatively affect the ability of Saccharomyces cerevisiae baker's yeast to leave the dough.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this result, it can be extrapolated that the spoilage point can be moved to a time point farther than 15 days on the storage time scale, especially when supplemented by a high dose of CFG. Resisting the increase in pH may mean reducing the contamination by the bacteria producing the basic substances (e.g., ammonia, amines) and restricting protein degradation [20,57]. The pH-reducing effect of CFG on minced beef at 100 µg g −1 is probably equivalent to the action of legumin and nisin at a higher concentration (200 µg g −1 ), as reported in [20].…”
Section: Discussionmentioning
confidence: 87%